Responses of Typical Riparian Vegetation to Annual Variation of River Flow in a Semi-Arid Climate Region: Case Study of China’s Xiliao River - Xiangzhao Yan; Wei Yang; Zaohong Pu; Qilong Zhang; Yutong Chen; Jiaqi Chen; Weiqi Xiang; Hongyu Chen; Yuyang Cheng; Yanwei Zhao (Land)
In semi-arid basins, riparian vegetation is an important part of the river ecosystem. However, with the decrease in river runoff caused by human activities and the continuous changes in climate, riparian vegetation has gradually degraded. To identify the main influencing factors of riparian vegetation changes, we extracted the river flow indicators, climate indicators, and riparian vegetation indicators of a Xiliao River typical section from 1985 to 2020 in spring and summer, and established a random forest model to screen the key driving factors of riparian vegetation. Then, we simulated the response characteristics of riparian vegetation to the key driving factors in spring and summer based on nonlinear equations. The results showed that the contribution of river flow factors to riparian vegetation was higher than that of climate factors. In spring, the key driving factors of riparian vegetation were the average flow in May and the average flow from March to May; in summer, the key driving factors were the average flow in May, the maximum 90-day average flow, and the average flow from March to August. Among them, the average flow in May contributed more than 50% to the indicators of riparian vegetation in both spring and summer. The final conclusion is that in the optimal growth range of plants, increasing the base flow and pulse flow of rivers will promote seed germination and plant growth, but when the river flow exceeds this threshold, vegetation growth will stagnate. The research results improve the existing knowledge of the influencing factors of riparian vegetation in semi-arid basins, and provide a reference for improving the natural growth of riparian vegetation and guiding the ecological protection and restoration of rivers in semi-arid areas.